ETHNOMEDICOZOOLOGICAL STUDIES ON THE INVERTEBRATES OF RAJASTHAN - SHARMA, VIJAY PRAKASH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
Ethnozoology express the inter relationship of tribal communities with faunal wealth of their environment, their interaction and evolution. Compared to animal drugs, there is a much public awareness of the utility of plants in medicinal systems like Aryuvedic, Unani & Homeopathy.